The Texts of Literacy Instruction: Obstacles to or Opportunities for Educational Equity?. (November 2017) - Hiebert, Elfrieda H.
Texts are a central part of reading. Yet our understandings of appropriate text features and distributions of text diets at different points in students' reading development are limited. The thesis of the essay is that, if the trajectory of struggling readers is to change, attention is needed to the features of texts and students' text diets, especially those of students who attend schools in heavily impacted communities. Three issues are identified that require the attention of researchers to ensure appropriate texts and text diets for struggling readers: (a) texts from the earliest levels need to be meaningful, (b) at least part of struggling readers' text diets need to be with texts in which words with morphological and phonological consistency are repeated, and (c) amount of text read by struggling readers needs to be substantial for reading capacity to increase. For each issue, the manner in which current practices can contribute to potential obstacles for struggling readers is described. Next, research on alternative practices is presented that shows how shifts in texts and text diets can support higher reading proficiency. The essay ends with a description of a research agenda that uses digital resources to increase students' facility with vocabulary in complex texts.